The mutagenic potential of 8-oxoG/single strand break-containing clusters depends on their relative positions - Noguchi, M; Urushibara, A; Yokoya, A; O'Neill, P; Shikazono, N (2012)
The biological consequences of clusters containing a single strand break and base lesion(s) remain largely unknown. In the present study we determined the mutagenicities of two- and three-lesion clustered damage sites containing a 1-nucleotide gap (GAP) and 8-oxo-7,8-dihydroguanine(s) (8-oxoG(s)) in . Escherichia coli. The mutation frequencies (MFs) of bi-stranded two-lesion clusters (GAP/8-oxoG), especially in . mutY-deficient strains, were high and were similar to those for bi-stranded clusters with 8-oxoG and base lesions/AP sites, suggesting that the GAP is processed with an efficiency similar to the efficiency of processing a base lesion or an AP site within a cluster. The MFs of tandem two-lesion clusters comprised of a GAP and an 8-oxoG on the same strand were comparable to or less than the MF of a single 8-oxoG. The mutagenic potential of three-lesion clusters, which were comprised of a tandem lesion (a GAP and an 8-oxoG) and an opposing single 8-oxoG, was higher than that of a single 8-oxoG, but was no more than that of a bi-stranded 8-oxoGs. We suggest that incorporation of a nucleotide opposite 8-oxoG is less mutagenic when a GAP is present in a cluster than when a GAP is absent. Our observations indicate that the repair of a GAP is retarded by an opposing 8-oxoG, but not by a tandem 8-oxoG, and that the extent of GAP repair determines the biological consequences. © 2012 Elsevier B.V.